Effect of Beverage Consumption Frequency on DMFT Index among Iranian Adult Population: An AZAR Cohort Study - Mahdi Hadilou; Mohammad Hossein Somi; Elnaz Faramarzi; Leila Nikniaz (International Journal of Dentistry)
Background. Given the effect of oral and dental condition on emotional and physical health and the different effects of beverage consumption on decayed, missing, and filled teeth (DMFT) as one of the indicators of oral health in different populations, this study aimed to investigate the effect of beverage consumption and its frequency on DMFT among Iranian adult population. Materials and Methods. The data of this cross-sectional study were obtained from AZAR (Azerbaijan) cohort, conducted on 15,006 adults aged 35 to 70 years old in Shabestar County, Iran. Demographic and nutritional data were collected by nutritionists through the “Food Frequency Questionnaire,” and DMFT index by general practitioners trained by a dentist according to the World Health Organization (WHO) guidelines. Beverages including milk, doogh, natural fruit juice, black tea, nonalcoholic beer, coffee, sugar-sweetened beverages, and artificial fruit juice were studied. Results. A total of 14,966 adults with the mean age of 49.64 ± 9.28 were enrolled. The participants’ mean DMFT value was 21.27 ± 8.95. Weekly consumption of tea and coffee beverages resulted in 13% (95% confidence interval: 3% to 22%) lower DMFT compared to daily consumption (p=0.01). However, there was no association between DMFT and other beverages. Conclusion. The higher DMFT values with the daily consumption of tea and coffee beverages showed that a part of adults’ oral health is affected by beverages; therefore, this should be considered by healthcare authorities in order to manage carries development in the communities.